Open Legal Policy dalam Putusan Mahkamah Konstitusi dan Perlindungan Hak Politik (Perspektif HAM dan Fiqh al-Siyasah) - Zainal Fanani (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2025)
This study attempts to trace the legal arguments of Constitutional Court Decision Number 62/PUU-XXII/2024 and its implications for the protection of political rights. This is motivated by the Constitutional Court's change in stance in deciding legal norms categorized as Open Legal Policy, as stated in the decision in question. This study is methodologically classified as normative legal research with an integrative approach between human rights law and fiqh al-siyasah. This study concludes that the Constitutional Court's shift in principles regarding Open Legal Policy in the decision reflects an effort to harmonize the paradigms of human rights law and fiqh al-siyasah in interpreting political rights as basic human rights. In this context, human rights values ​​oriented towards human dignity and the principle of maqasid al-shari'ah, which emphasizes the welfare of the people, combine to form a moral-ethical basis for upholding Indonesian constitutionalism.